1
$\begingroup$

enter image description here

I tried breaking the terms into differences or finding a generalised term but did not get it right. Can someone please help me to proceed with this?

$\endgroup$
  • $\begingroup$ Are you sure the first term is $2$, and not $1$? $\endgroup$ – Clement C. Nov 4 '17 at 22:08
0
$\begingroup$

Assuming the first term is $1$ (and not $2$ as written), the general term of the series is, for $n\geq 1$, $$ a_n \stackrel{\rm def}{=} \frac{\prod_{k=2}^{n}(2k+1)}{n!3^{n-1}} = \frac{\prod_{k=1}^{n}(2k+1)}{n!3^{n}} = \frac{(2n+1)!}{n!3^{n}\prod_{k=1}^n(2k)} = \frac{(2n+1)!}{n!3^{n}2^nn!} = \frac{(2n+1)!}{(n!)^26^{n}} $$ or, equivalently, $a_n= \binom{2n}{n}\left(\frac{1}{6}\right)^n$.

Now, either you work towards finding the general form for $$f(x) = \sum_{n=1}^\infty (2n+1) \binom{2n}{n}x^n$$ (a power series with radius of convergence $1/4$), which you can find by relating it to both $ g(x) = \sum_{n=1}^\infty n\binom{2n}{n}x^{n-1} $ (recognize a derivative) and $ h(x) = \sum_{n=1}^\infty \binom{2n}{n}x^{n} $, since $$f(x) = 2xg(x)+h(x)\,;$$ or, by other means (there may be?) you establish that $f(1/6) = 3\sqrt{3}$, leading to $$ \sum_{n=1}^\infty a_n = 3\sqrt{3}. $$

$\endgroup$
  • $\begingroup$ If $n=1$, the product is empty, not 5 since it goes from 2 to $n$. $\endgroup$ – marty cohen Nov 4 '17 at 22:43
  • $\begingroup$ @martycohen for $n=1$, you get 1, the purported first term. $n=2$ gives 5/(6.3) $\endgroup$ – Clement C. Nov 4 '17 at 22:45
  • $\begingroup$ Sorry, the last part above should of course read 5/6, which matches the 5/(2! 3) from the question. I blame typing on my phone. $\endgroup$ – Clement C. Nov 4 '17 at 23:26
  • $\begingroup$ @martycohen but the question says first term=2 and can you please help me with the third step on how you managed the question or can you do it in simple terms without any complex terms (radius of convergence). I would be very grateful to you :) $\endgroup$ – Aditya Singh Nov 5 '17 at 7:08
  • $\begingroup$ @AdityaSingh take the result, remove 1 (my first term), add 2 (your first term). $\endgroup$ – Clement C. Nov 5 '17 at 15:06

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.